ANALISIS KOMPETENSI, PROFESIONALISME DAN ETOS KERJA TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA NEGERI 45 PALEMBANG - Yonita Jane Kasih; Fakhry Zamzam; Neny Rostiati (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2020)
This study aims to determine and analyze how the Competency Analysis, Professional and Work Ethic on the Performance of 45 Palembang State Junior High School Teachers. The research sample consisted of 50 samples of teachers and academic staff at SMP Negeri 45 Palembang and were selected by purposive sampling. Questionnaire and interview data were conducted at SMP Negeri 45 Palembang. The data analysis technique used linear regression analysis techniques. In this study, the liquidity variable was measured using Competence, Professional and Work Ethic. Hypothesis testing used multiple analysis techniques with the SPSS version 22 application. Testing data using the t test, that competence has a significant positive effect on teacher performance with t count 5,834> t table 2,003, there is a positive professional effect on teacher performance with 5,906> t table 2,003 and there is an influence of work ethic on teacher performance with 7,790> t table 2,003 and Competence, Professionalism and Work Ethic influence on Teacher Performance with F count 18,617> F table 2,003. The results showed that partially the disclosure of competence has a positive and significant effect on performance. While partially Professional has a positive and significant effect on performance. And partially Work Ethic has a positive and significant effect on Performance Simultaneously, the influence of Competence, Professionalism and Work Ethics has a positive and significant effect on Teacher Performance with the coefficient of determination (R2) regression together with the influence of competence, professionalism and work ethic on teacher performance. only 0.623 or 62.3%. This means that as much as 27.7% is influenced by variations or combinations of other variables outside the research variables. Meanwhile, the exogenous variable with the highest influence on performance is work ethic with a regression coefficient of 0.747.